Emission characteristics of diesel engines fuelled with B20 with different DPF, DOC and EGR arrangements - Nagaprasad K.S.; Banapurmath N.R.; Madhu D.; Soudagar M.E.M.; Mujtaba M.A.; Kalam M.A.; Vadlamudi C.; Krishnappa S. (Taylor and Francis Ltd., 2025)
In the present investigation, pre- and post-combustion techniques are adopted for diesel engines. This work focuses on optimisation of engine performance powered with biodiesel B20 blend by incorporating pre- and post-combustion techniques addressing emission from diesel engines within acceptable norms. In pre-combustion techniques, Karanja biodiesel with two proportions (B10 and B20) is injected along with diesel and exhaust gas recirculation with varied flow rates is used to address NOx emissions. A diesel particulate filter (DPF) and diesel oxidation catalyst (DOC) are fitted in the exhaust pipe of the engine. Initial test runs were conducted on engine using diesel with 0%, 5%, 10% and 20% EGR when DPF and DOC are positioned according to three arrangements. After optimising position of EGR, DPF and DOC, the engine was fuelled with B10 and B20 to study performance and emissions at different EGR rates with and without these devices. Results indicated changes in overall performance with injection of biodiesel; reduction in unburnt hydrocarbon by 43.9%, smoke by 71.15%, NOx by 22.6% for 20% biodiesel fuelled engine with 10% EGR, DPF and DOC. B20 can be fuelled into diesel engine with suitable modifications, least emissions can be achieved with 10% EGR, DPF and DOC. ? 2023 Informa UK Limited, trading as Taylor & Francis Group.